Copper as a potential adjunct therapy for critically ill COVID-19 patients. (December 2020) - Fooladi, Shahnaz; Matin, Somaieh; Mahmoodpoor, Ata
Summary: COVID-19 is a major health problem affecting all people worldwide and has a high mortality rate especially in critically ill patients. Although much is known about its different clinical symptoms, there are significant knowledge gaps about its pathology and cellular responses to the virus. Copper plays an essential role in respiration, immune function and free-radical defense. Despite its important action in physiochemical properties, only small amount of copper is presented in biological fluid, none of which presents as free ion form that readily affirms its depletion in critically ill patients. Recent studies confirmed its anti-viral capacity. Closer understanding of copper signaling, its vulnerability, method of assessment and interpretation, administration rout and dosage opens up new perspectives regarding therapeutic copper administration against critically ill COVID-19 patients. So, it seems that physicians should consider copper insufficiency in their critically ill COVID-19 patients. However, an attention should be paid to copper toxicity and estimating the adverse responses depending on copper dose or severity of copper limitation, as well as the duration of copper misbalance.